Climate change and social vicissitudes in China over the past two millennia. Issue 2 (September 2016) - Yin, Jun; Su, Yun; Fang, Xiuqi
Abstract: The relation between climate change and historical rhythms has long been discussed. However, this type of study still faces the lack of high-resolution data concerning long-term socio-economic processes. In this study, we collected 1586 items of direct and proffered evidence from 29 Chinese history books. We used semantic analysis to reconstruct a quantitative series of the social vicissitudes of the past 2000 yr with a 10-yr resolution to express the phase transition of the social vicissitudes of the dynasties in China. Our reconstruction demonstrates that social vicissitudes have clear cyclical features on multiple time scales. Analysis of the association of social rise and fall with climate change indicates that temperature displayed more significant effects on social vicissitudes in the long term, while precipitation displayed more significant effects on the social vicissitudes in the short term. There are great overlaps between social and climatic variables around the predominant or periodic bands. Social rise mostly occurred in the centennial-scale warm periods, whereas social decline mostly occurred in the centennial-scale cold periods. Under warm-wet conditions, social rise occurred over 57% of the time; under cold-dry conditions, the social decline occurred over 66% of the time.